2016
DOI: 10.1159/000451046
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Properties of Candidate Oncogenes in Chromosome Region 17p11.2p12 in Human Osteosarcoma

Abstract: Osteosarcomas are primary tumors of bone that most often develop in adolescents. They are characterized by complex genomic changes including amplifications, deletions, and translocations. The chromosome region 17p11.2p12 is frequently amplified in human high grade osteosarcomas (25% of cases), suggesting the presence of one or more oncogenes. In previous studies, we identified 9 candidate oncogenes in this region (GID4, ARGHAP44, LRRC75A-AS1, TOP3A, COPS3, SHMT1, PRPSAP2, PMP22, and RASD1). The aim of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Previous studies have revealed that COPS3 promotes osteosarcoma cell migration and invasion [ 31 ], and suppression of COPS3 could inhibit growth and induce apoptosis in lung cancer and hepatocellular carcinoma [ 32 , 33 ]. However, our data clearly show that COPS3 silencing did not significantly inhibit osteosarcoma growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that COPS3 promotes osteosarcoma cell migration and invasion [ 31 ], and suppression of COPS3 could inhibit growth and induce apoptosis in lung cancer and hepatocellular carcinoma [ 32 , 33 ]. However, our data clearly show that COPS3 silencing did not significantly inhibit osteosarcoma growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data clearly show that COPS3 silencing did not significantly inhibit osteosarcoma growth in vivo. Moreover, overexpression of COPS3 did not significantly enhance cell proliferation, although its overexpression markedly increased cell migration and invasion in osteosarcoma SAOS-2 cells [ 31 ]. Therefore, we reason that COPS3 might function in a cell type-dependent manner concerning its role in the growth of cancer cells, whereas it mainly acts to promote metastasis in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A novel lncRNA LRRC75A-AS1 (also named SNHG29) located at 17p11.2 has 892 bp in length. Previously, LRRC75A-AS1 was reported to has oncogenic properties 15 . Besides, LRRC75A-AS1 has been validated in glioblastoma, and it regulates the miR-223-3p/CTNND1 axis to promote glioblastoma through Wnt/β-catenin pathway 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these candidates, changes in the expression level of Lrrc75a-as1 influenced calcium deposition in VSMCs. In previous studies, Lrrc75a-as1 was shown to be expressed in normal villous maturation, human osteosarcoma, breast cancer, and gastric cancer tissues 4548 . Lrrc75a-as1 was also predicted as a prognostic factor in acute myeloid leukemia based on statistical analysis 49 .…”
Section: Discussionmentioning
confidence: 92%